Regulation 1215/2012: prorogation of jurisdiction and special jurisdiction of Article 7.1, Regarding verbal commercial concession agreement. : Commentary of Judgment of the Court, 8 marzo 2018, saey home, c-64/17 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In this judgment, one more time, the Court of Justice studies the validity of a submission agreement that is included in the conditions of sale to which the contract entered into between the parties does not expressly refer. Once analyzed the submission forum of Regulation 1215/2012, the Court studies the application of the special forum on contractual matters of the article 7.1 to international commercial concession contract. The European judicial court classifies the distribution contract as contract for the provision of services for the purposes of the letter b) of the aforementioned precept. The obliga-tion to provide the service is identified as the provision by the concessionaire, that is, the distribution in Spain of the products that are the object of the contract. Finally, once it is known that the provision of the service to be taken into account must be the one for the concessionaire, instead of concluding that the Spanish jurisdiction has the competence, the European judicial explains the theory on the determination of the place of provision of services in the case in which there is a plurality of places of execution of the same; scenario that does not raise the factual assumption under study.
Keywords: Validity of a jurisdiction clause; verbal agreement without written confirmation; prorogation of jurisdiction; special jurisdiction art. 7.1; Regulation 1215/2012; commercial concession agreement; provision of services; place of performance of provision of services